Long-term observations of radiation-induced creatinine clearance reduction and renal parenchymal volume atrophy. Issue 1 (July 2016) - Inaba, Koji; Okamoto, Hiroyuki; Wakita, Akihisa; Tsuchida, Keisuke; Kashihara, Tairo; Kobayashi, Kazuma; Harada, Ken; Kitaguchi, Mayuka; Sekii, Shuhei; Umezawa, Rei; Takahashi, Kana; Murakami, Naoya; et al.
Abstract: Purpose: The kidney is a dose-limiting organ for upper abdominal radiotherapy. In this study, radiation-induced kidney injury represented by changes of creatinine clearance (Ccr) and renal parenchymal volume measured by computed tomography (CT) were evaluated by analysing dose–volume histograms (DVHs) in patients with primary gastric diffuse large B-cell lymphoma (PGDLBCL) treated with chemoradiotherapy. Materials and methods: Thirty-eight PGDLBCL patients (seventy-six kidneys) treated with chemoradiotherapy were included in this study. At least 4 years of follow-up was required for eligibility. Patients underwent (immuno-) chemotherapy followed by radiotherapy with approximately 40 Gy to the whole stomach and perigastric lymph nodes. Ccr and CT were obtained at least annually. Changes of Ccr and renal parenchymal volume before and 4 years after radiotherapy were compared using DVH parameters. Results: Mean Ccr decreased significantly from 82.7 mL/min (range, 39–124 mL/min) before radiotherapy to 70.4 mL/min (range, 35–109 mL/min) ( p = 0.01) 4 years after radiotherapy. Mean reduction of bilateral renal parenchymal volume was 12% (range, −5–37%) in the same time period. Ccr and renal parenchymal volume tended to lower over time more than 4 years after radiotherapy. Concerning DVH analysis, V20Gy ⩾ 26.6% and D30% ⩾ 19 Gy had a significant risk of bilateral renal atrophy of ⩾14% and reduction of the Ccr ⩾ 20 mL/min. Conclusion: This study revealed that there was a definite relationship between DVH, renal atrophy and Ccr reduction. V20Gy < 26.6% and D30% < 19 Gy appeared to be safe dose constraints for a Ccr reduction of <20 mL/min 4 years after radiotherapy.